(3OhQ GdJcfjc aj GdEYdGe GdOhdj (B:s (3OQGSI fXQjI h JWHjbjI (B/s - (3GdYhjfj, eMeO Ydjs ((3GdbGgQI (B:s (3YGde GdcJH ,s, 1979)
(3jJfGhd GdcJGH OhQ GdJcfjc aj GdEYdGe GdOhdj HTcd eJejR jLeY Hjf GdfXQjI h GdJWHjb ef NdGdQHW GdJcfjc HYfGUQ GdYedjI GdEYdGejI h GdCNdGb h OQGSI dMGdGJ JWHjbjI eSJeOI ef hGbY GdefWbI(B. (3hgPG GeQ dG Zfi Yfg ddeTJZdjf HGdGYdGe h GdSjGSI GdNGQLjI h QLGd GdSjGSI h GdOGQSjf Hd h GdQLd GdYGOj GdPj jhGLg HhSGFd GdGYdGe aj cd ecGf h cd hbJ eeG jSGYO aj age GaVd ddGYdGe Pdc GdYde GdLOjO GdPj jbhe HOhQ GNWQ GdGOhGQ aj YGde Gdjhes
Keywords: (3GdEYdGe GdOhdjs; (3GdJcfjcs